The Prevalence of Psychiatric and Chronic Pain Comorbidities in Fibromyalgia: an ACTTION systematic review - Kleykamp, Bethea A.; Ferguson, McKenzie C.; McNicol, Ewan; Bixho, Ida; Arnold, Lesley M.; Edwards, Robert R.; Fillingim, Roger; Grol-Prokopczyk, Hanna; Turk, Dennis C.; Dworkin, Robert H. (Seminars in arthritis and rheumatism, 2021)
•Over half of FM patients had a diagnosis of depression in their lifetime.•Depression and chronic pain conditions involving head/jaw pain and IBS were elevated among FM patients compared to other chronic pain populations.•Addressing comorbid health conditions in clinical trials of treatments for FM can increase the generalizability and real-world application of research findings. Fibromyalgia (FM) is a chronic widespread pain condition that overlaps with multiple comorbid health conditions and contributes to considerable patient distress. The aim of this review was to provide a systematic overview of psychiatric and chronic pain comorbidities among patients diagnosed with FM and to inform the development of recommendations for the design of clinical trials. Thirty-one, cross-sectional, clinical epidemiology studies that evaluated patients diagnosed with FM were included for review. None of the reviewed studies reported on the incidence of these comorbidities. Sample size-weighted prevalence estimates were calculated when prevalence data were reported in 2 or more studies for the same comorbid condition. The most prevalent comorbidity across all studies reviewed was depression/major depressive disorder (MDD) with over half of the patients included having this diagnosis in their lifetime (weighted prevalence up to 63%). In addition, nearly one-third of FM patients examined had current or lifetime bipolar disorder, panic disorder, or post-traumatic stress disorder. Less common psychiatric disorders reported included generalized anxiety disorder, obsessive compulsive disorder, and specific phobias (agoraphobia, social phobia). There were fewer studies that examined chronic pain comorbidities among FM patients, but when evaluated, prevalence was also high ranging from 39% to 76% (i.e., chronic tension-type or migraine headache, irritable bowel syndrome, myofascial pain syndrome, and temporomandibular disorders). The results of the review suggest that depression and chronic pain conditions involving head/jaw pain and IBS were elevated among FM patients compared to other conditions in the clinic-based studies. In contrast, anxiety-related disorders were much less common. Addressing the presence of these comorbid health conditions in clinical trials of treatments for FM would increase the generalizability and real-world applicability of FM research.